Are you happy or 高兴? Differences in affective word perception between first and second languages of Chinese-English bilinguals - Liew, Ming En (Nanyang Technological University, 2020)
The linguistic relativity theory proposed by Sapir and Whorf has been widely studied over the years. However, these studies have not ventured into the territory of emotion research, which is a fairly new field of inquiry within psycholinguistics. This paper thus seeks to explore the linguistic relativity theory and whether, or how, it applies to bilingualism and emotion word perception. The research questions posed in this paper are as follows: (1) Do Singaporean English-Chinese bilinguals process emotional words in their L1 more strongly as compared to their L2?; (2) Does language proficiency affect bilinguals’ perception of emotional words in their L1 and L2; and (3) Does the language environment they learnt the language in and the language environment they are exposed to now affect bilinguals’ perception of emotional words in their L1 and L2? Overall, results generally supported the theory. Various factors were proposed to explain contradictions in this study as compared to past literature. These factors include language proficiency, age of acquisition, and emotional context, among others. Finally, limitations of the paper were addressed, future directions proposed, and possible real-life implications of this research was raised.